Genes related to mitochondrial functions are differentially expressed in phosphine-resistant and -susceptible Tribolium castaneum. (December 2015) - Oppert, Brenda; Guedes, Raul; Aikins, Michael; Perkin, Lindsey; Chen, Zhaorigetu; Phillips, Thomas; Zhu, Kun; Opit, George; Hoon, Kelly; Sun, Yongming; Meredith, Gavin; Bramlett, Kelli; et al.
Abstract Background Phosphine is a valuable fumigant to control pest populations in stored grains and grain products. However, recent studies indicate a substantial increase in phosphine resistance in stored product pests worldwide. Results To understand the molecular bases of phosphine resistance in insects, we used RNA-Seq to compare gene expression in phosphine-resistant and susceptible laboratory populations of the red flour beetle, Tribolium castaneum . Each population was evaluated as either phosphine-exposed or no phosphine (untreated controls) in triplicate biological replicates (12 samples total). Pairwise analysis indicated there were eight genes differentially expressed between susceptible and resistant insects not exposed to phosphine (i.e., basal expression) or those exposed to phopshine (>8-fold expression and 90 % C.I.). However, 214 genes were differentially expressed among all four treatment groups at a statistically significant level (ANOVA, p  < 0.05). Increased expression of 44 cytochrome P450 genes was found in resistant vs. susceptible insects, and phosphine exposure resulted in additional increases of 21 of these genes, five of which were significant among all treatment groups (p  < 0.05). Expression of two genes encoding anti-diruetic peptide was 2- to 8-fold reduced in phosphine-resistant insects, and when exposed to phosphine, expression was further reduced 36- to 500-fold compared to susceptible. Phosphine-resistant insects also displayed differential expression of cuticle, carbohydrate, protease, transporter, and many mitochondrial genes, among others. Gene ontology terms associated with mitochondrial functions (oxidation biological processes, monooxygenase and catalytic molecular functions, and iron, heme, and tetrapyyrole binding) were enriched in the significantly differentially expressed dataset. Sequence polymorphism was found in transcripts encoding a known phosphine resistance gene, dihydrolipoamide dehydrogenase, in both susceptible and resistant insects. Phosphine-resistant adults also were resistant to knockdown by the pyrethroid deltamethrin, likely due to the increased cytochrome P450 expression. Conclusions Overall, genes associated with the mitochondria were differentially expressed in resistant insects, and these differences may contribute to a reduction in overall metabolism and energy production and/or compensation in resistant insects. These data provide the first gene expression data on the response of phosphine-resistant and -susceptible insects to phosphine exposure, and demonstrate that RNA-Seq is a valuable tool to examine differences in insects that respond differentially to environmental stimuli.